Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fpls.2015.00980
|View full text |Cite
|
Sign up to set email alerts
|

A Large Family of AvrLm6-like Genes in the Apple and Pear Scab Pathogens, Venturia inaequalis and Venturia pirina

Abstract: Venturia inaequalis and V. pirina are Dothideomycete fungi that cause apple scab and pear scab disease, respectively. Whole genome sequencing of V. inaequalis and V. pirina isolates has revealed predicted proteins with sequence similarity to AvrLm6, a Leptosphaeria maculans effector that triggers a resistance response in Brassica napus and B. juncea carrying the resistance gene, Rlm6. AvrLm6-like genes are present as large families (>15 members) in all sequenced strains of V. inaequalis and V. pirina, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 63 publications
2
45
0
Order By: Relevance
“…The parameters (default) used were those that resulted in the AvrLm6-like proteins forming a cluster with the same members as when clustered manually [45]. The clusters were manually inspected and those members with a similar cysteine pattern retained.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters (default) used were those that resulted in the AvrLm6-like proteins forming a cluster with the same members as when clustered manually [45]. The clusters were manually inspected and those members with a similar cysteine pattern retained.…”
Section: Methodsmentioning
confidence: 99%
“…Other scab fungi are pathogenic on various tree hosts, including Fusicladium effusum on pecan, F. oleaginum on olive, V. populina on poplar, V. saliciperda on willow and V. fraxini on ash, among many others (Sivanesan, 1977;Zhang et al, 2011;Young et al, 2018). Despite being economically important pathogens, the genetic basis of the interactions between scab fungi and their respective hosts remains poorly understood (Singh et al, 2005;Steiner and Oerke, 2007;Kucheryava et al, 2008;Bowen et al, 2009;Mesarich et al, 2012;Cooke et al, 2014;Shiller et al, 2015;Deng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…pomi, V. inaequalis f. sp. eriobotrya, V. pirina and F. effusum, and they revealed that V. inaequalis strains tend to have a higher repeat content compared to other species, with up to 47% of their genome sequence covered by repetitive elements (Shiller et al 2015;Bock et al, 2016;Deng et al, 2017 ;Passey et al, 2018). These studies highlighted in Venturia genomes the expansion of putative effector gene families, genes that are known to determine plantfungus interactions (Shiller et al, 2015;Deng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations